Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s11703-007-0075-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salicylic acid (SA) on delaying fruit senescence of Huang Kum pear

Abstract: This experiment was undertaken to explore the effect of salicylic acid (SA) at different concentrations on regulating fruit senescence of Huang Kum pear. Through dipping fruits and fruit discs for a series of hours in SA solution, enzyme activities and physiological characteristics of Huang Kum pear were determined. The results revealed that SA enhanced the activity of superoxide dismutase (SOD) and peroxidase (POD) enzymes at 0.02 mmol/L and at 0.002 mmol/L with the treatment of dipping fruit discs for 4 h an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 9 publications
(16 reference statements)
3
15
0
1
Order By: Relevance
“…Values of h° declare the colour changes from green to yellow of peel, according to Taiz and Zeiger (2010) ethylene is the responsible for ripening changes in fruit including colour changes by manage pigments synthesis, The green colour of the unripe fruit is due to the existence of chlorophylls, and the increase of different colours during ripening is due to the disappearance of these pigments and the synthesis of carotenoids, in this way salicylic delay colour changes. Imran et al, (2007) obtained similar results in pear cv. Huang Kum treated by salicylic at 0.1 mM, in addition to Champa et al (2015) in grapes cv.…”
Section: Instrumental Colour (Hue Angle Value)supporting
confidence: 69%
“…Values of h° declare the colour changes from green to yellow of peel, according to Taiz and Zeiger (2010) ethylene is the responsible for ripening changes in fruit including colour changes by manage pigments synthesis, The green colour of the unripe fruit is due to the existence of chlorophylls, and the increase of different colours during ripening is due to the disappearance of these pigments and the synthesis of carotenoids, in this way salicylic delay colour changes. Imran et al, (2007) obtained similar results in pear cv. Huang Kum treated by salicylic at 0.1 mM, in addition to Champa et al (2015) in grapes cv.…”
Section: Instrumental Colour (Hue Angle Value)supporting
confidence: 69%
“…8). The plausible reason for increasing the crop yield might be due to delayed senescence of plant organs (particularly leaves and flowers) in response to exogenous SA (Imran et al, 2007) that will automatically help the plant in extending the duration of photosynthetically active sites and also prevent the premature loss of flowers and fruits. This consequently resulted in the observed increase in the number of pods per plant (Tab.…”
Section: Proline Content In Leavesmentioning
confidence: 99%
“…The oxidative enzymes play an important role in induced resistance by the oxidation of phenols to oxidized toxic products (quinone) which limit fungal activity. Also, peroxidase catalyze the final polymerization step of lignin synthesis, which increase the ability of tissue to lignify which may restrict the fungal penetration [36], [37], [38], [39]. Marra, et al [40] observed that, when both Trichoderma and the pathogen were interacting with the plant, several PRproteins were up-regulated less than by the pathogen alone.…”
Section: A Effect Of T Harazianum As a Biotic Inducer On Peroxidasementioning
confidence: 99%